Design Thinking in Software Testing Planning - Pérez Vera, Yasiel (2020)
This article presents the possibility of working on software development using not only agile methodologies for processes but also the use of Design Thinking for the planning of the Software Test Plan. Since during the software management process there is the difficulty of understanding the software, for one of the stages of the software management, in this case, the planning of the software tests, the tester needs to know what the user requires, due to Because the software product is intangible and difficult to measure, the tester must listen to the end-user and perform the tests according to the requirements requested. To improve the process of understanding what the user really requires, its pillars are used as empathy, collaboration, and prototyping for a better interpretation, which will allow obtaining an assertive attitude to the tester. On the other hand, we have to carry out the software test plan, based on this a study was carried out on the possibility of using Design Thinking to help the software test planning process.